Interests, identities, and institutions in the politics of regional economic construction in East Asia - Batalla, Eric Vincent C. (Animo Repository, 2020)
This essay examines the politics of regional economic construction in East Asia based on the comparative politics framework of Kopstein and Lichbach (2009). The framework highlights three important aspects of domestic politics, namely: Interests, identities, and institutions and relates these aspects to the global (or regional) context. The essay stresses the importance of domestic politics to regional affairs and therefore, should be considered in future assessments of the prospects of regional economic construction. It suggests a research agenda in aid of ongoing regionalization processes. © 2010 Copyright 2010 by Koninklijke Brill NV, Leiden, The Netherlands.